2014
DOI: 10.1152/japplphysiol.01129.2013
|View full text |Cite
|
Sign up to set email alerts
|

Stressor-induced increase in muscle fatigability of young men and women is predicted by strength but not voluntary activation

Abstract: This study investigated mechanisms for the stressor-induced changes in muscle fatigability in men and women. Participants performed an isometric-fatiguing contraction at 20% maximal voluntary contraction (MVC) until failure with the elbow flexor muscles. Study one (n = 55; 29 women) involved two experimental sessions: 1) a high-stressor session that required a difficult mental-math task before and during a fatiguing contraction and 2) a control session with no mental math. For some participants (n = 28; 14 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 54 publications
8
74
0
1
Order By: Relevance
“…We previously showed that young women (18-30 years) and not men had greater fatigability and decreased steadiness during a sustained isometric contraction with the elbow flexor muscles when high CD was imposed but not low CD [16,38]. The current study was designed to identify whether older men and women increased fatigability and decreased steadiness during submaximal isometric fatiguing contractions with the elbow flexor muscles.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…We previously showed that young women (18-30 years) and not men had greater fatigability and decreased steadiness during a sustained isometric contraction with the elbow flexor muscles when high CD was imposed but not low CD [16,38]. The current study was designed to identify whether older men and women increased fatigability and decreased steadiness during submaximal isometric fatiguing contractions with the elbow flexor muscles.…”
Section: Discussionmentioning
confidence: 90%
“…The greater fatigability when high CD was imposed during the isometric sustained contractions in young adults was associated with baseline strength [16] such that weaker individuals were more susceptible to increased fatigability, possibly as a result of altered muscle perfusion [11,12,16]. This was achieved because we were able to match some of the male and female cohort for strength [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations